A meta-analysis of the economic value of forest carbon stock - Asif Raihan; Rawshan Ara Begum; Mohd Nizam Mohd Said (Penerbit Universiti Kebangsaan Malaysia, 2021)
Global climate change has become a critical issue due to the global greenhouse gases (GHGs) emissions dominated by carbon dioxide (CO2). Forest ecosystems are becoming increasingly essential in mitigating climate change by absorbing the atmospheric CO2 and storing it in tree biomass, a process known as carbon sequestration. Decades of environmental valuation research show that forest carbon has a positive economic impact. Economic valuation of forest carbon provides mechanism for climate change mitigation policy instruments, compare rival forestry and environmental initiatives, and infuse public willingness to pay in forest conservation projects. It is also required for carbon trading, conservation, and management of the forests. However, carbon storage estimates in forest ecosystems throughout the world differ substantially. Thus, this study conducts a global meta-analysis to estimate the marginal economic value of forest carbon per hectare. A systematic review of scientific literature leads to the selection of 60 primary studies from 30 different countries published between 1990 to 2021. The meta-analysis identified wide variations in economic values of forest carbon across the globe. The outcome of the meta-analysis reveals that global economic value of forest carbon is USD2005 per hectare. This study provides an insight on the marginal economic value of global forest carbon which would be helpful to understand the necessity of avoiding deforestation and conserving more forested areas that ultimately helps to mitigate global climate change through emission reduction.